A Theoretically‐Guided Optimization of a New Family of Modular P, S‐Ligands for Iridium‐Catalyzed Hydrogenation of Minimally Functionalized Olefins. Issue 38 (5th August 2014) - Margalef, Jèssica; Caldentey, Xisco; Karlsson, Erik A.; Coll, Mercè; Mazuela, Javier; Pàmies, Oscar; Diéguez, Montserrat; Pericàs, Miquel A.
Abstract A library of modular iridium complexes derived from thioether‐phosphite/phosphinite ligands has been evaluated in the asymmetric iridium‐catalyzed hydrogenation of minimally functionalized olefins. The modular ligand design has been shown to be crucial in finding highly selective catalysts for each substrate. A DFT study of the transition state responsible for the enantiocontrol in the Ir‐catalyzed hydrogenation is also described and used for further optimization of the crucial stereodefining moieties. Excellent enantioselectivities (enantiomeric excess (ee) values up to 99 %) have been obtained for a range of substrates, including E‐ and Z‐trisubstituted and disubstituted olefins, α, β‐unsaturated enones, tri‐ and disubstituted alkenylboronic esters, and olefins with trifluoromethyl substituents.